Low‐Temperature Interfacial Polymerization and Enhanced Electro‐Responsive Characteristic of Poly(ionic liquid)s@polyaniline Core‐shell Microspheres. Issue 17 (7th August 2018) - Zheng, Chen; Liu, Yang; Dong, Yuezhen; He, Fang; Zhao, Xiaopeng; Yin, Jianbo
Abstract: The synthesis of monodisperse poly(ionic liquid)s (PILs) microspheres coated with semiconducting polyaniline (PANI) shell is reported, which shows enhanced electro‐responsive electrorheological (ER) effect but decreased power consumption compared to neat PIL microspheres. The monodisperse PIL microspheres are first prepared via dispersion polymerization and then PANI is coated via low‐temperature interfacial polymerization of aniline on the surface of hydrophobic PIL microspheres without additional modification. The stimulus‐responsive ER effect of the core‐shell microspheres when dispersing in insulating oil are investigated under electric fields. The power‐law of yield stress versus electric field strength and the dielectric relaxation spectroscopy are analyzed to understand the ER effect and the origin of property enhancement. It demonstrates that the semiconducting PANI shell can well limit the irreversible ion leakage of PIL microspheres and improve the particle polarizability, resulting in decreased power consumption but enhanced electro‐responsive ER effect. Abstract : Monodisperse poly(ionic liquid)s@polyaniline core‐shell microspheres are synthesized via a low‐temperature interfacial polymerization and show enhanced electro‐responsive electrorheological effect but decreased power consumption compared to neat poly(ionic liquid)s microspheres due to the semiconducting polyaniline shell, which can limit the irreversible ion leakage of poly(ionic liquid)s microspheres and improve particle polarizability.